Factors Affecting Delayed Referral for Speech Therapy in Iranian children with Speech and Language Disorders - Roshanak Vameghi; Mahnaz Haji-Bakhtiari; Nikta Hatami-Zadeh; Akbar Biglarian; Mohammad Reza Rah-Chamani (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Early detection of children who are at risk for speech and language impairment and those at early stages of delay is crucial for provision of early intervention services. However, unfortunately in Iran, this disorder is not identified or referred for proper treatment and rehabilitation at early critical stages. Materials & Methods: This study was carried out in two phases. The first phase which was qualitative in nature was meant to identify all potentially affective factors through literature review as well as by acquiring the viewpoints of experts and families on this issue. Twelve experts and 9 parents of children with speech and language disorders participated in semi-structured in-depth interviews, thereby completing the first draft of potentially affective factors compiled through literature review. The completed list of factors finally led to the design of a questionnaire for identifying "factors affecting late referral in childhood speech and language impairment". The questionnaire was approved for face and content validity. The cronbach's alpha was determined to be 0.81. Two groups of parents were asked to complete the questionnaire: the parents of children who had attended speech and language clinics located on the west and central regions of Tehran city, after their child was 3 years old and those who had attended before their child was 3 years old, as the case and control group, respectively. Results: According to the results, among the seven factors which showed significant difference between the two groups of children before definite diagnosis of speech and language disorders was arrived for the child, 3 factors were related to the type of guidance and consultation received by the family from physicians, 2 factors were related to parents' lack of awareness and knowledge, and 2 factors were related to the screening services received. All six factors showing significant difference between the two groups after definite diagnosis of speech and language disorders was arrived for the child were somehow related to the parents' misbeliefs and incorrect attitude towards the issue. Conclusion: We suggest that executive managers in the field of child health promote awareness programs for families in order to increase their knowledge and correct their beliefs and attitudes, and also to implement complementary training programs for pediatricians and other physicians related to the field of child health.